Concentration Sensor Design Using Wavelength Shift Based Photonic Crystal Fibre - Alawsi, Suha Mousa Khorsheed (Iraqi Journal of Science, 2018)
The proposed sensor is designed to measure the concentration of liquids using the photonic crystal fibre (PCF) principles. The sensor has been implemented by splicing the two ends of the PCF piece to a single mode fibre (SMF). The air holes found in the splicing points are fully collapsed by the arc discharge. The wavelength shift occurs at the collapsed regions due to the excitation of combined core besides the cladding modes. The PCF was infiltrated by diluted olive oil to be tested in terms of the variation of sensing response with the wavelength shift in the transmission spectra. The sensitivity is 875 nanometre per refractive index unit (nm/RIU) that estimated in refractive index range between 1.43 and 1.47. Result also shows that the sensor has a small temperature sensitivity of 0.863dBm/°C in the range of 20°C to 70°C. The proposed concentration sensor potentially can be applied in biomedical, biological and chemical applications.